2021
DOI: 10.1108/jsit-07-2020-0132
|View full text |Cite
|
Sign up to set email alerts
|

Role of interaction quality and trust in use of AI-based voice-assistant systems

Abstract: PurposeThe rapid growth of artificial intelligence (AI)-based voice-assistant systems (VASs) has created many opportunities for individuals to use VASs for various purposes in their daily lives. However, traditional quality success factors, such as information quality and system quality, may not be sufficient in explaining the adoption and use of AI-based VASs. This study aims to propose interaction quality as an additional, yet more important quality measure that leads to trust in an AI-based VAS and its adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Though these conceptions are quite distinct, they all suggest that AI is an attempt to create machines capable of executing intelligent tasks. AI is booming today (Lee et al , 2021) and is being touted as an efficient tool in different areas, namely, banking (Eren, 2021), human resource management (Kshetri, 2021), tourism and hospitality (Go et al , 2020) and online retailing (Chen et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though these conceptions are quite distinct, they all suggest that AI is an attempt to create machines capable of executing intelligent tasks. AI is booming today (Lee et al , 2021) and is being touted as an efficient tool in different areas, namely, banking (Eren, 2021), human resource management (Kshetri, 2021), tourism and hospitality (Go et al , 2020) and online retailing (Chen et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Naturally, researchers have attempted to identify the characteristics that enhance VAs' trustworthiness. Some notable characteristics include the ability to display emotions, personalities and social capabilities (Hamacher et al, 2016; Lee et al, 2021; Qiu & Benbasat, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As it stands, people report not using voice assistants for a broad range of tasks, even though they're technically capable of doing so [27]. Prior work has illustrated the importance of trust for continued voice assistant use [31,35], as trust is pivotal to user adoption of voice assistants [33,45] and willingness to broaden the scope of voice assistant tasks [27]. It is especially important to support trust-building between users and voice assistants as researchers continue to imagine and develop new capabilities for them, including complex tasks such as supporting healthcare tasks [41,55], giving mental health advice [52,66], and other high stakes decision-making [17].…”
Section: User Expectations and Trust In Voice Assistantsmentioning
confidence: 99%
“…Prior researchers have examined trust in machines in terms of people's confidence in a machine's ability to perform as expected, benevolence (well-meaning), and integrity to adhere to ethical standards [36] Broadly, past research has evaluated how various factors such as accuracy and errors affect people's trust in algorithms [19,20,67]. In the case of voice assistants, Nasirian et al [45] and Lee et al [33] studied how quality affects trust in and adoption of voice assistants, and found that information and system quality did not impact users' trust in a voice assistant, but interaction quality did. Interaction quality was captured based on a study by Ekinci and Dawes [22], in which Likert scale responses were captured regarding competence, attitude, service manner, and responsiveness of the voice assistant.…”
Section: User Expectations and Trust In Voice Assistantsmentioning
confidence: 99%